Tumor-targeting domains for chimeric antigen receptor T cells. (January 2017) - Bezverbnaya, Ksenia; Mathews, Ashish; Sidhu, Jesse; Helsen, Christopher W; Bramson, Jonathan L
Immunotherapy with chimeric antigen receptor (CAR) T cells has been advancing steadily in clinical trials. Since the ability of engineered T cells to recognize intended tumor-associated targets is crucial for the therapeutic success, antigen-binding domains play an important role in shaping T-cell responses. Single-chain antibody and T-cell receptor fragments, natural ligands, repeat proteins, combinations of the above and universal tag-specific domains have all been used in the antigen-binding moiety of chimeric receptors. Here we outline the advantages and disadvantages of different domains, discuss the concepts of affinity and specificity, and highlight the recent progress of each targeting strategy.